POTENSI SERANGAN KELOMPOK CRUSTACEA DI SEMAI MANGROVE DESA MENDALOK KALIMANTAN BARAT - Simangunsong, Muhammad Iqbal; Ekyastuti, Wiwik; Oramahi, H A (Universitas Tanjungpura, 2019)
Information about infestation potential of Crustacean in mangrove Mendalok village in West Kalimantan is unknown. The purpose of this study was to identify the spesies of Crustacean that attacked mangrove seeds and to investigated their level of destruction by crustacean mangrove forest. This research was carried out for 4 weeks in the field. This method uses a survey method with a single plot technique. Plots made of 16 plots with a size of 5x5 m considering the discovery of a nest and the problem of destruction due to Crustaceans and shelter / nest containing holes. Three types of pest were found, from the famili Grapsidae, Sesarmidae and Ocypodidae. The average percentage of plants attacked is 8.07. The average attack rate of 7.04 attacks includes the mild category. The average level of damage of all plot is 7.05 of these attacks included in the mild category.Keyword: Crustacean, Mangrove, Seedling